Responsibility of Companies Declared Bankrupt for Employee Wages - Adiyata Segara Pradhana; Iswi Hariyani; Firman Floranta Adonora (Rechtenstudent, 2024)
Employment or labor problems never end over time, from issues of protection, wages, welfare, industrial relations disputes, guidance and labor inspections, companies along the way do not always experience stable growth and a company can even experience bankruptcy. This research will focus on discussing what is the status of employee wages when the company is declared bankrupt?; Can objects with collateral rights to third parties be included as bankruptcy assets? Using normative juridical research methods and collaborating with the statutory approach and case approach, the answer was found, namely the judge's consideration at the cassation level in decision Number 625 K/Pdt.Sus-Pailit/2021 when correlated with article 102 paragraph 1 of Law Number 40 of 2007 concerning Limited Liability Companies. Every company must comply with the requirements of the company law and its implementing regulations. This element shows that the company adheres to a closed system. Apart from its unique characteristics, a Limited Liability Company also has advantages, including: As a result of limited liability, if the company has debt, shareholders are only responsible for the amount of capital they have paid in. A limited liability company is a legal entity. So that the continuity of the company as a legal entity is guaranteed even though the owner has changed.